Pengaruh Program Edukasi Berbasis Peer Education terhadap Tingkat Pengetahuan Remaja Putri Terkait Pemeriksaan Payudara Sendiri - Latifatun Nisa; Qomariyah Qomariyah; Kristina Maharani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Breast carcinoma, commonly known as breast cancer, is a type of malignancy that occurs in the milk-producing ducts and sacs of the breast. Breast cancer is the second leading cause of death in Indonesia, after lung cancer. One of the early steps in detecting breast cancer is through breast self-examination (BSE). Although BSE can help detect lumps or abnormalities in the breast, many adolescent girls are unaware of how to perform this examination or its importance. One reason for this is the lack of education regarding the correct method and the significance of performing BSE regularly. Therefore, an effective educational approach is needed, such as peer education, where peers provide information to their fellow students about the importance of self-breast examination. The purpose of this study is to analyze the impact of a peer education program on improving adolescent girls' knowledge of BSE. This research uses a quantitative method with a quasi-experimental design, specifically a one-group pretest-posttest design. The population in this study consisted of female students from grades X and XII at SMK Nurul Islami Semarang, with a sample of 35 students selected through simple random sampling. Data collection was carried out using a questionnaire that included questions about the students' knowledge of self-breast examination. The results were analyzed using the Wilcoxon test, which showed an Asymp Sig (2-tailed) value of 0.000, which is smaller than 0.05. This indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning there is a significant effect of the peer education program on increasing adolescent girls' knowledge of BSE. The findings of this study suggest that peer education is an effective method for raising awareness among adolescent girls about the importance of early breast cancer detection, thus encouraging them to perform self-breast examinations more regularly.